1999
DOI: 10.1115/1.2823544
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rotating Cavitation in a Finite Pitch Cascade Using a Closed Cavity Model and a Singularity Method

Abstract: A new method is proposed for the stability analysis of cavitating flow. In combination with the singularity method, a closed cavity model is employed allowing the cavity length freely to oscillate. An eigen-value problem is constituted from the boundary and supplementary conditions. This method is applied for the analysis of rotating cavitation in a cascade with a finite pitch and a finite chordlength. Unlike previous semi-actuator disk analyses Watanabe et al., 1997a), it is not required to input any informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 14 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…The higher order rotating cavitation and higher order cavitation surge occur at higher flow rate than the design flow rate. As we decrease the flow rate, these instabilities start to occur at higher cavitation number, as predicted by the analysis (Watanabe et al, 1999;Horiguchi et al, 2000).…”
Section: Figurementioning
confidence: 82%
See 1 more Smart Citation
“…The higher order rotating cavitation and higher order cavitation surge occur at higher flow rate than the design flow rate. As we decrease the flow rate, these instabilities start to occur at higher cavitation number, as predicted by the analysis (Watanabe et al, 1999;Horiguchi et al, 2000).…”
Section: Figurementioning
confidence: 82%
“…However, Watanabe et al (1999) and Horiguchi et al (2000) theoretically predicted the higher order rotating cavitation which has higher propagation speed ratio (about 3-6). In the present study, the higher order rotating cavitation with a propagation speed ratio of about 5 is reported.…”
mentioning
confidence: 95%
“…We have developed a simple analysis of unsteady cavitating flow combining a free streamline theory and a singularity method, and succeeded in simulating the cavitation instabilities of hydrofoil (Watanabe et al [9]) as well as those of cascade such as rotating cavitation and cavitation surge (Watanabe et al [10]). More recently, we have constructed an analytical method of the thermodynamic effect on steady, partially cavitating flow (Watanabe et al [11]).…”
Section: Introductionmentioning
confidence: 99%
“…Kawata et al [11] showed an example in which the negative gradient of the pressure performance curve under quasi-steady conditions becomes positive under unsteady conditions due to the phase delay. Brennen and Acosta [4], Otsuka et al [12], Watanabe et al [13], and Rubin [14] showed that the mass flow gain factor and the cavitation compliance have the phase delay under the unsteady conditions. Therefore, the unsteady characteristics of performance curves and cavitation characteristics are important to discuss the stability of the hydraulic system.…”
Section: Introductionmentioning
confidence: 99%